Effect of bond exchange rate on dynamics and mechanics of vitrimers. Issue 21 (5th August 2021) - Perego, Alessandro; Khabaz, Fardin
Abstract: Thermoset polymers are classified amongst the most challenging materials to recycle due to the permanent crosslinks that increase their strength and stiffness compared to their thermoplastic counterparts. Vitrimers provide a promising route to achieve the recyclability of thermosets by implementing dynamic covalent bonds within the network. In this study, a hybrid molecular dynamics (MD)‐Monte Carlo (MC) technique is used to simulate these adaptive networks constructed by a coarse‐grained model. The model proposed in this work describes the dynamic nature of the covalent bonds while maintaining a constant crosslink density. As this framework also shows flexibility in accommodating various exchange reaction activation energy via adjusting the energy difference in MC step, the dynamic and mechanical properties of the vitrimer system are intensely affected by the number of successful bond exchanges happening at every step. In both rubbery and glassy regimes, lowering the energy barrier of the bond exchange reaction results in enhanced motion for the vitrimer segments. This enhanced mobility, in turn, directly affects the stress–strain relationship of these networks, where a higher number of exchanges results in larger deformation before fracture even at low temperatures. Furthermore, the stress distribution in vitrimers shows more homogenous distribution before failure than in the thermoset network. Abstract :